(untitled) (Global Journal of Management and Business Research, 2022)
Customer preference is ever changing yet it is very integral in hospitality industry. This study will help us to compare both the restaurant and understand about the services getting in the hotel. It is very important for us to firstly understand why we need to work on negative as well as positive guest experience because the hotel generate most of its revenue from different core operation area in which guest interaction is must. Menu is a type of format in a paper form which give us details about the F